NICE guidelines and the epilepsies: how should practice change?. Issue 6 (19th May 2006) - Dunkley, C; Cross, J H
Abstract : The care and provision for children and adults with epilepsy and their carers has recently been under scrutiny with a series of reports highlighting concerns and calling for change. The National Institute for Clinical Excellence (NICE) published recommendations for management of adults and children in October 2004. Although recommendations were often specific and practical they did not include precise details regarding their implementation. Key recommendations and their implications are discussed in this review.